Alternatively fuelled vehicles (Professional Engineering Pub. for the Institution of Mechanical Engineers, 2000)
Annotation A collection of nine contributions that cover such topics of alternative fuel technologies as liquified petroleum gas, electric and hybrid vehicles, fuel cells. Specific subjects discussed include clean fuel technology, alkaline fuel cells for road traction, manufacturing challenges of alternative fuelled vehicles (AFCs), and the development of the AFC market. All of the discussions of policy and programs are drawn from the UK. Distributed by ASME. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Based on the one-day seminar Alternatively Fuelled Vehicles, held at the National Exhibition Centre, Birmingham, UK, on 10 November 1999.
Keywords: Spark ignition engines -- Alternative fuels -- Congresses.; elektronické knihy; electronic books